OP0230 Predictors of hypogammaglobulinemia during rituximab maintenance therapy in rheumatoid arthritis: a 12-year longitudinal multi-centre study. (12th June 2018) - Boleto, G; Avouac, J.; Wipff, J.; Forien, M.; Dougados, M.; Roux, C.; Kahan, A.; Dieudé, P.; Allanore, Y.
Abstract : Background: Rituximab (RTX) is an anti-CD20 monoclonal antibody that selectively depletes B-cell population. One of the drawbacks of a prolonged peripheral B-cell depletion is the suppression of protective antibodies and an increased risk for infectious events. However, few long-term data are available on predictors for the development of low levels of serum immunoglobulins in patients receiving repeated courses of RTX. Objectives: We aimed at the identification of predictors for hypogammaglobulinemia occurrence in RA patients long-term treated with RTX in a 'real-life' setting. Methods: Multicenter longitudinal observational usual care study including RA patients according to ACR 1987 and/or ACR/ EULAR 2010 classification criteria followed and treated with RTX. A previous study assessing the safety profile of RTX in patients with RA reported a median follow-up of 30 months. 1 Therefore, we decided to include RA patients on RTX maintenance therapy, after a minimal exposition of 30 months. Serum protein electrophoresis was performed before each RTX infusion. Hypogammaglobulinemia and severe hypogammaglobulinemia were defined as total gammaglobulin <6 g/L and <4 g/L, respectively. Safety monitoring included the collection of all adverse events (AE) in particular severe infections. Results: 134 patients met inclusion criteria: 113 female subjects (84.3%); mean age 52.1±11.4 years. Mean follow-up was 79.5±24.6 months and analysis was based on 854.9 patient-years (pt-yrs). Mean RTX cumulative dose was 12.0±4.9 g. Hypogammaglobulinemia (<6 g/L) occurred during the follow-up period in 23 patients (2.7 events per 100 pt-yrs), leading to an incidence of 17.1%. The mean time to development of hypogammaglobulinemia was 64±23 months. A total of 9.7% of patients had severe infections (1.5 events per 100 pt-yrs). Patients who developed hypogammaglobulinemia were more likely to experience severe infections (26.1% vs 6.3%, p=0.033). Univariate Cox analysis identified age over 65 years (HR 4.28 [95% CI: 0.92 to 19.97], p<0.001), low gammaglobulin levels prior the first RTX infusion (<8 g/L) (HR 7.35 [95% CI: 1.82 to 29.68], p<0.001) as predictors of protective factor (HR 0.26 [95% CI: 0.08 to 0.87], p=0.03). Conclusions: Our results show that gammaglobulin levels of less than 8 g/L at baseline is a strong independent risk factor for developing subsequent hypogammaglobulinemia, whereas concomitant MTX therapy seems to be a protective factor in RA patients treated long-term with RTX. Identifying such predictors will raise clinicians' awareness and allow more tailored monitoring of RA patients long-term treated with RTX. Reference: [1] Isvy, et al. Joint Bone Spine2012. Disclosure of Interest: None declared